2006
DOI: 10.1590/s0073-47212006000100013
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive isolation among three populations of the genus Grammostola from Uruguay (Araneae, Theraphosidae)

Abstract: ABSTRACT. Ethological isolation of individuals from three allopatric Grammostola populations of Uruguay, G. iheringi (Keyserling, 1891), G. mollicoma (Auserer, 1875) northern population and G. mollicoma southern population, was tested under laboratory conditions. Grammostola iheringi behaved as a reproductive isolated species, whereas the two populations of G. mollicoma did not show ethological isolation between them. However, ecological isolating reproductive mechanisms could be acting on G. mollicoma popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…) and behaviour. As such, it is the integration of the genetic, phylogenetic and phenotypic results, including behavioural differences (Costa & Pérez‐Miles ; Postiglioni & Costa ) which suggests that G. anthracina as currently understood is composed of two species; one corresponding to the black morph and other to the brown‐reddish morph. Even when the black morph and the brown‐reddish morph clades show internal structure, most of these subclades lack significant support and, more importantly, there are not morphologic differences among them.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…) and behaviour. As such, it is the integration of the genetic, phylogenetic and phenotypic results, including behavioural differences (Costa & Pérez‐Miles ; Postiglioni & Costa ) which suggests that G. anthracina as currently understood is composed of two species; one corresponding to the black morph and other to the brown‐reddish morph. Even when the black morph and the brown‐reddish morph clades show internal structure, most of these subclades lack significant support and, more importantly, there are not morphologic differences among them.…”
Section: Resultsmentioning
confidence: 99%
“…coexisting at the same locality. Postiglioni & Costa () suggested that the absence of overlapping is mainly due to ecological factors. We also consider that usually theraphosids have poor vagility (Ferretti et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, current biogeographical barriers such as the Uruguay River between Argentina and Uruguay, and the Negro River within Uruguay (Fig. 1), could be important causes of divergence among the groups analyzed (Postiglioni & Costa 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to identify geographic factors that cause these variations and to separate these factors from genotypic effects, it is known that local and clinal variations in genitalic characters do exist (Lachaise et al 1981;Hribar 1994;Tatsuta & Akimoto 1998;Kelly et al 2000;Jennions & Kelly 2002;Tatsuta et al 2001). Studies performed in different groups of insects and arachnids have shown that populations of a single species can begin differentiating both morphologically and genetically as a result of allopatric distribution, reaching reproductive isolation afterwards (Yamashita & Polis 1995;Postiglioni & Costa 2006;Holwell 2008).…”
mentioning
confidence: 99%